The Mongol Empire and its Legacy - Amitai-Preiss, Reuven,; Morgan, (Brill Book Archive Part 1, ISBN: 9789004472495., 1999)
The Mongol empire was founded early in the 13th century by Chinggis Khan and within the span of two generations embraced most of Asia, becoming the largest land-based state in history. The united empire lasted only until around 1260, but the major successor states continued on in the Middle East, present day Russia, Central Asia and China for generations, leaving a lasting impact - much of which was far from negative - on these areas and their peoples. The papers in this volume present new perspectives on the establishment of the Mongol empire, Mongol rule in the eastern Islamic world, Central Asia and China, and the legacy of this rule. The various authors approach these subjects from the view of political, military, social, cultural and intellectual history. This publication has also been published in paperback, please click here for details.